Negative Association of Interleukin-33 Plasma Levels and Schistosomiasis Infection in a Site of Polyparasitism in Rural Cameroon - Kamdem, Severin Donald; Konhawa, Francis; Kuemkon, Erve Martial; Meyo Kamguia, Leonel; Tchanana, Gladys K.; Nche, Frungwa; Oumarou, Alim; Hamza, Mamadou; Ouratou, Yasmine; Tcheutchoua, Mariette Nzoku; Ghislain Essomba, René; Ngogang, Marie Paule; et al. (Frontiers in Immunology, 2019)
Background: This study aimed to investigate the association of plasma levels of IL-33, a mucosal alarmin known to elicit type-2 immunity, with infection and liver fibrosis profiles of school children from an endemic area for Schistosoma mansoni, malaria and hepatitis (B & C) in rural Cameroon. Methods: A cross-sectional study enrolling schoolchildren from 5 public schools was conducted. Single schistosomiasis, malaria and hepatitis infections or co-infections were assessed by kato katz, microscopy, and rapid diagnostic tests, respectively. Hepatic fibrosis was assessed by ultrasound according to WHO Niamey guidelines and plasma levels of Interleukin 33 were determined by ELISA. All statistics were performed using R studio software. Principal findings: We found a prevalence of 13.5% (37/275), 18.2% (50/275), and 8% (22/275), respectively for schistosomiasis, malaria and hepatitis (B or C) single infections. Only 7.6% (21/275) of co-infections were reported. Although Plasma IL-33 showed a minimal negative risk for schistosomiasis infection (AOR 0.99; 95% CI 0.97–1.01), S. mansoni infected participants had lower levels of plasma IL-33 (p = 0.003) which decreased significantly as eggs burdens increased (p = 0.01) with a negative Pearson coefficient of r = −0.22. Hepatic fibrosis occurred in 47.3% (130/275) of our study population independently from plasma levels of IL-33 (AOR 1.00; 95% CI 0.99–1.01). Conclusion/Significance: Our data failed to show an association between plasma IL-33 levels and liver disease but convincingly report on a negative association between plasma IL-33 levels and schistosomiasis infection and egg burden in school children from a polyparasitic schistosomiasis endemic area.